Some growth characteristics of yellow-mouth turban shell (Turbo chrysostomus) in Ly Son Islands - Quang Ngai Province - Hua , Thai Tuyen; Hua, Thai An; Thai , Minh Quang; Mai , Xuan Dat; Nguyen, Le Thao My (Vietnam Journal of Marine Science and Technology, 2025)
Focusing on the species Turbo chrysostomus, the study examined aspects of distribution, growth characteristics and resource management strategies. Turbo chrysostomus mainly inhabits low water areas to coral reefs with a depth of 8 meters. The average Turban Shell height is 47.51 mm. The theoretical maximum size is 76.9 mm with growth factor K = 1.17, and the monthly growth rate in the first year is 5.36 mm. The correlation between the height (H) and weight (Wm) of the snail is H = -0.001*Wm + 0.8822. Notably, its growth pattern is uneven, with height increasing faster than weight. Worryingly, wild mussel populations are showing signs of decline, requiring resource management measures. Proposed solutions include eliminating the capture of small snails and avoiding development in key breeding areas, particularly Chua Hang and Hang Cau, to ensure the sustainability of the snail resource into the future.